Evaluación de la calidad del aire mediante un laboratorio móvil: Puente Aranda (Bogotá D.C., Colombia) - Palacio Soto, Daniel Fabián; Zafra Mejía, Carlos Alfonso; Rodríguez Miranda, Juan Pablo (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
The locality of Puente Aranda in Bogotá has been reported as a zone of high air pollution, mainly because the PM10 concentrations exceed the legal limits. This paper presents a temporal and spatial assessment of air quality in the industrial zone of Puente Aranda locality by using a mobile laboratory of monitoring. Air pollutants measured by the laboratory during the sampling period (2009/04/13-2009/12/21) were the following: PM10, NOx, NO2, NO, SO2, CO and O3. With regard to the Colombian law, the results show that PM10 (24 hours) is the air pollutant with the highest number of exceedances during the investigation period (47.3%), however, the evaluation of the exceptional state by air pollution shows that the highest concentrations reported not generate a level of prevention; above, in contrast with the results obtained by use of the air quality index proposed by the U.S. Environmental Protection Agency. On the other hand, the findings suggest a similar trend in the temporal behavior of PM10, O3 and NOx over the whole of the research area; that is, probably by the existence of dominant sources in the industrial area of the locality. Finally, the concentrations recorded (PM10, NO2, NOx, NO and CO) by the mobile laboratory (central area) are on average 2.30 and 2.01 times higher than those recorded by stations mobile SDA (eastern area) and fixed SDA (western area), respectively.